Pemberdayaan Berbasis Lingkungan: Penguatan Branding Eco-Green pada Wisata Alam Dua Musim di Desa Tambakrejo, Kecamatan Krembung, Kabupaten Sidoarjo - Fierda Nurany; Ria Dini Apriliasari; Muhammad Rafi Arkan R; Bintang Poetra Rizky; Farah Elfiyah; Malfa Fauziana; Salsabila Putri Widyadarani; Achmad Zakaria Rachman; Aditya Adam Varizky; Nabila Rizky Syahputri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
The development of an environment-based tourism village is one of the strategic efforts in improving community welfare while preserving nature. Tambakrejo Village, Krembung District, Sidoarjo Regency, has the potential for natural tourism through Two-Season Nature Tourism in Awar-awar Hamlet. This area has an attraction in the form of seasonal lakes and distinctive natural landscapes, but before the service activities are carried out, it still faces problems in the form of suboptimal area arrangements, weak visual identity, and limited public understanding of the concept of eco-green tourism. This condition is the background for the implementation of community service activities by the KKN 011 Prabaswara team at Bhayangkara University Surabaya in 2025. The purpose of this service activity is to strengthen the management of Two-Season Nature Tourism through strengthening the branding of tourist villages, implementing the eco-green concept, and empowering local communities as the main actors in tourism management. The implementation method is carried out in a participatory manner by involving village officials, tourism managers, and the community in educational activities and area planning. The results of the activity show that there are significant changes in the physical and social aspects of the tourist area. Physically, the area became more organized through the planting of ornamental plants, the construction of eco-friendly photo spots from recycled materials, and the installation of tourist information boards. From the social side, the public has experienced an increased understanding of the importance of the eco-green concept, waste reduction, and the role of branding in attracting tourists. The involvement of residents in mutual cooperation activities also fosters a sense of belonging and commitment to maintaining tourism sustainability. Based on these results, it is recommended to strengthen digital promotion, increase the institutional capacity of tourism managers, and develop advanced programs so that Two-Season Nature Tourism can develop sustainably and competitively.